159k views
3 votes
1) A.B+B.C.A.D+A.D
2) A.D+B.C+A.C.B.C.D
3)B.C+A.C.B+A.D​

User JPetric
by
5.0k points

1 Answer

4 votes

Step-by-step explanation:

Draw AE⊥BC

In △AEB and △AEC, we have

AB=AC

AE=AE [common]

and, ∠b=∠c [because AB=AC]

∴ △AEB≅△AEC

⇒ BE=CE

Since △AED and △ABE are right-angled triangles at E.

Therefore,

AD2=AE2+DE2 and AB2=AE2+BE2

⇒ AB2−AD2=BE2−DE2

⇒ AB2−AD2=(BE+DE)(BE−DE)

⇒ AB2−AD2=(CE+DE)(BE−DE) [∵BE=CE]

⇒ AB2−AD2=CD.BD

AB2−AD2=BD.CD

1) A.B+B.C.A.D+A.D 2) A.D+B.C+A.C.B.C.D 3)B.C+A.C.B+A.D​-example-1
User Ayush Khare
by
5.3k points